The systemic complications of ulcerative colitis. Issue 515 (September 1968) - Watkinson, Geoffrey
Abstract : A brief review of some of the systemic lesions of ulcerative colitis has been made. In 465 patients seen between 1948 and 1963 in Leeds, skin lesions occurred in 6·2%, colitic arthritis in 12·0%, sacro-iliitis in 18% and spondylitis in 6%. Eye lesions developed in 4% and liver disease in 2%. The significance of some of these lesions has been reviewed.